Investigation of surface-modified EBM printed Ti-6Al-4V alloys for biomedical applications - DEMİRCİ, SELİM; TÜNÇAY, MEHMET MASUM; GÜLLÜOĞLU, ARİF NİHAT (My University, 2022)
This work aimed to comprehensively assess the influence of various surface modifications on the formation of apatite ability for EBM Ti-6Al-4V alloy. Sandblasting (S), acid-etching (E), sandblasting and acid-etching (SE), anodization (NA), micro-arc oxidations in 1 M H2SO4 solution (SM) and 1 M H3PO4 solution (PM) methods were applied to modify electron beam melted (EBM) Ti-6Al-4V surface. The alpha/alpha\"-Ti structures and TiO2 phases were detected by XRD. The surface roughness (Ra) values ranged from 0.25 mu m and 2.86 mu m. The wettability of samples was between around 25 degrees and 104 degrees The SM sample possessed the lowest contact angle. In vitro tests were employed in the simulated body fluid (SBF) solution for 28 days. The samples with different surface textures demonstrated bioactive behaviors. In vitro test results showed that apatite layers formed on the surfaces. The SM sample exhibited good apatite formation ability when the Ca/P ratios were considered. The apatite formation for the SM sample might derive from high roughness, low contact angle value, the existence of Ti-OH groups, and anatase and rutile phases. The SM can be implemented to boost bioactivity on EBM Ti-6Al-4V alloys.
Keywords: Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Kimya; Fizikokimya; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Chemistry; Physical Chemistry; Natural Sciences; Engineering and Technology; KİMYA, FİZİKSEL; Temel Bilimler (SCI); MALZEME BİLİMİ, KAPLAMALAR VE FİLMLER; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); FİZİK, UYGULAMALI; FİZİK, YOĞUN MADDE; CHEMISTRY, PHYSICAL; CHEMISTRY; Natural Sciences (SCI); MATERIALS SCIENCE, COATINGS & FILMS; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); PHYSICS, APPLIED; PHYSICS; PHYSICS, CONDENSED MATTER; Yüzeyler ve Arayüzler; İstatistiksel ve Doğrusal Olmayan Fizik; Yoğun Madde Fiziği; Yüzeyler, Kaplamalar ve Filmler; Elektronik, Optik ve Manyetik Malzemeler; Genel Malzeme Bilimi; Fiziksel ve Teorik Kimya; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Surfaces and Interfaces; Statistical and Nonlinear Physics; Condensed Matter Physics; Surfaces, Coatings and Films; Electronic, Optical and Magnetic Materials; General Materials Science; Physical and Theoretical Chemistry; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Additive manufacturing; Electron beam melting; Ti-6Al-4V; Surface modification; Bioactivity; BONE-LIKE APATITE; BEAM MELTED TI-6AL-4V; MECHANICAL-PROPERTIES; TITANIUM; HYDROXYAPATITE; BIOACTIVITY; TI; MICROSTRUCTURE; LUBRICATION; IMPROVEMENT